A NEW APPROACH TO PH OF POINT OF ZERO CHARGE MEASUREMENT: CRYSTAL-FACE SPECIFICITY BY SCANNING FORCE MICROSCOPY (SFM) - A NEW APPROACH TO THE MEASUREMENT OF ADSORPTION ISOTHERMS AT THE SOLID-LIQUID INTERFACE - Eggleston C.M.; Jordan G. (My University, 1998)
The pH of point of zero charge (pHpzc) is a fundamentally important property used in modeling the interaction of solid surfaces with aqueous solutions and solutes. The pHpzc is normally measured by acid-base titration of solid suspensions. Here, a scanning force microscope (SFM) is used to measure forces of repulsion or attraction between chemically tailored tips and quartz (101) and hematite (001) surfaces, as a function of tip-surface separation and pH. The force at contact (FAC) is at a minimum near the expected point of pHpzc for a chemically similar tip and sample. The results are compared to predicted interaction forces from a simple DLVO model, which shows that the SFM technique for pHpzc measurement is most promising for surfaces (such as iron oxides) that have not-too-widely spaced pKa1 and pKa2 values for surface site deprotonation. However, improvements in precision will be necessary to fully utilize the technique.The SFM approach to pHpzc measurement may in future allow the measurement of crystal-face-specific pHpzc, rather than a weighted average of all exposed surface sites, and thus allow us to ask better-defined structure-reactivity questions for mineral surfaces. The approach can in theory be extended to the single-site scale in order to probe the properties (e.g., potential and charge) of individual terrace, step, or kink sites.